1995
DOI: 10.1172/jci117704
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal properties of murine intestinal phospholipase A2.

Abstract: We purified a molecule from the murine small intestine that killed both Escherichia coli and Listeria monocytogenes, and identified it as intestinal phospholipase A2 (iPLA2) by NH2-terminal sequencing and enzymatic measurements. The ability of iPLA2 to kill. L monocytogenes was greatly enhanced by 5 mM calcium, inhibited by EGTA and abolished after reduction and alkylation, suggesting that enzymatic activity was required for iPLA2-mediated bactericidal activity. A mouse-avirulent phoP mutant, S. typhimunium 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
149
0
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(156 citation statements)
references
References 55 publications
4
149
0
3
Order By: Relevance
“…We propose that PA colonization improves this elimination by increasing sPLA2-IIA expression of airways cells. In agreement, previous studies showed that sPLA2-IIA is present in human and animal biological fluids or cell supernatants at sufficient levels to kill bacteria 21,[53][54][55][56] . AMPs such as LL-37 have also been shown to play a role in pulmonary host defense toward SA and PA in CF lungs 57 , although the antimicrobial activity of these AMPs is impaired in CF airways [57][58][59] .…”
Section: Discussionsupporting
confidence: 91%
“…We propose that PA colonization improves this elimination by increasing sPLA2-IIA expression of airways cells. In agreement, previous studies showed that sPLA2-IIA is present in human and animal biological fluids or cell supernatants at sufficient levels to kill bacteria 21,[53][54][55][56] . AMPs such as LL-37 have also been shown to play a role in pulmonary host defense toward SA and PA in CF lungs 57 , although the antimicrobial activity of these AMPs is impaired in CF airways [57][58][59] .…”
Section: Discussionsupporting
confidence: 91%
“…This molecule has proinflammatory and bactericidal activity (35) and has been isolated in the inflamed mucosa of patients suffering from inflammatory bowel disease (36) as well as in the circulation of patients suffering from septic shock (37). We quantified phospholipase A 2 in the intestinal mucosa and in the intestinal fluid of the CD14-blocked and control rabbits exposed to Shigella, but found no differences between the two groups of rabbits with respect to secretory phospholipase quantities (data not shown).…”
Section: Discussionmentioning
confidence: 97%
“…PGLYRPs require Ca 2ϩ and N-glycosylation for bactericidal activity, which are not usually required by membrane-permeabilizing antibacterial peptides, such as defensins or magainin (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). PGLYRPs are bactericidal (kill 99% of bacteria) at 0.1-1 M, and thus are more active than most antibacterial peptides, such as defensins or magainin (1-6, 37), but less active than phospholipase A 2 , which is the most active human bactericidal peptide (1-4, 7).…”
Section: Discussionmentioning
confidence: 99%
“…Besides forming a mechanical barrier, these tissues and their secretions are rich in antimicrobial peptides (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), including defensins (1-6), phospholipase A 2 (7), dermicidin (8), cathelicidin (9), RNases (10), and psoriasin (11). Antimicrobial peptides are low molecular weight amphipathic molecules that kill microorganisms by damaging their membranes (1)(2)(3)(4).…”
mentioning
confidence: 99%